Longitudinal metagenomics reveals continuous restructuring of soil pathobiome under persistent Phytophthora pressure - Basu, Umer; Ahanger, Shafat Ahmad; Gai, Xiaotong; Hu, Xiaoping (Frontiers in Plant Science, 2026)
Soil borne pathogen, Phytophthora nicotianae causes black shank disease in tobacco, present a pervasive threat to global agriculture, with conventional control strategies often proving inadequate. A critical gap exists in our understanding of the long-term, dynamic interplay between the pathogen and the soil microbiome. To address this, we conducted a six-year longitudinal metagenomic study in a monocultured tobacco field, revealing a pathobiome in constant, non-equilibrium adaptation. Our analysis uncovered profound microbial restructuring, beginning with cumulative transcriptional reprogramming of highly significant genes. Functional profiling showed a critical metabolic shift toward anabolic capacity, with a 66.7% increase in KEGG orthologs and enrichment of amino acid biosynthesis (+8.9%), ribosomes (+13.0%), and quorum sensing (+11.0%). The soil resistome underwent dramatic succession, featuring an initial coordinated defense (R²=0.825), a comprehensive collapse in Year 3-4 (917 downregulated genes), and a resilient recovery that drove a net increase in antibiotic resistance, indicating a lasting ecosystem alteration. Virulence factor evolution revealed strategic trade-offs, with flagella systems dominating (2,583 occurrences) while more costly energy consuming secretion systems declined, and 87 core virulence factors persisted across time. Crucially, we observed a widespread decoupling between genetic potential and functional expression; key categories for defense and signal transduction declined in abundance (slopes of -150.4 and -264.9, respectively) despite stable gene counts, suggesting a systemic, energy conserving survival strategy. Concurrently, the community experienced progressive diversity loss (Shannon index slope = -0.0464/yr at genus level) despite maintained species richness (717 species), indicating restructuring was driven by shifting evenness rather than species loss. Our findings exhibit that persistent pathogen pressure drives the soil microbiome into a continuous state of adaptive restructuring, prioritizing coordinated defensiveness and metabolic efficiency over stability. This time resolved framework challenges static views of soil ecosystems and provides a foundational dataset for developing predictive, microbiome informed strategies to manage soil borne diseases sustainably.